Selection by seed weight improves traits related to seedling establishment in Panicum coloratum L. var. makarikariense - Giordano, Mabel Cristina; Berone, German Dario; Tomas, Maria Andrea (Wiley, 2019)
Selection for heavy seed was implemented to overcome establishment problems in Panicum coloratum var. makarikariense. A collection covering the genetic diversity of the species available in Argentina was used as a base population (BP), and two cycles of recurrent phenotypic selection to increase seed weight were performed. Seedlings, obtained from seeds from each cycle and the BP, were further evaluated in the greenhouse. An increase of 17% in mean seed weight was obtained after two cycles of recurrent selection. No differences in germination or emergence were detected among the selected materials and the BP. However, seedlings from selected materials were taller and showed higher leaf elongation rate, adventitious roots elongation rate and total growth rate than that from BP. This research also revealed that in P. coloratum var. makarikariense, more vigorous seedlings can be selected from genotypes that produce heavier seeds.